2021
DOI: 10.3390/diagnostics11050871
|View full text |Cite
|
Sign up to set email alerts
|

Association of Early Renal Dysfunction with Lipid Profile Parameters among Hypertensives in Kazakhstan

Abstract: Dyslipidemia plays an essential role in chronic kidney disease (CKD). The role of lipids and lipoproteins in the early pre-disease state of CKD in hypertensive patients is still unclear. The study aimed to evaluate the relationship between early renal dysfunction and lipid profile parameters among hypertensive patients in Kazakhstan. From April 2015 to December 2016, 800 Kazakh males and females with primary hypertension who met the inclusion criteria were included in this cross-sectional study. Data were coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 52 publications
(51 reference statements)
0
1
0
Order By: Relevance
“…A comprehensive assessment of the association between decreased eGFR and lipid variables in Kazakh hypertensives reported that serum ApoB level is significantly negatively associated with the early pre-CKD condition, and the final model was still significantly fitted even after adjustment of confounding factors, including diet, age, quality score and income ( 36 ). Hence, for patients with different comorbidities, the associations of increased serum ApoB level transitions with the development of CKD, and whether comorbidities can modify the effect are worth exploring.…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive assessment of the association between decreased eGFR and lipid variables in Kazakh hypertensives reported that serum ApoB level is significantly negatively associated with the early pre-CKD condition, and the final model was still significantly fitted even after adjustment of confounding factors, including diet, age, quality score and income ( 36 ). Hence, for patients with different comorbidities, the associations of increased serum ApoB level transitions with the development of CKD, and whether comorbidities can modify the effect are worth exploring.…”
Section: Discussionmentioning
confidence: 99%